A study on environmental impact of insulation thickness of poultry building walls. (1st May 2018) - Küçüktopcu, Erdem; Cemek, Bilal
Abstract: In this paper, the optimum insulation thicknesses, energy savings, payback periods and emission rates of CO2 were determined for poultry buildings in the cities of Antalya, Samsun, Ankara and Erzurum, located in different climates of Turkey. The calculations were made considering five different fuels (coal, fuel-oil, natural gas, LPG and electricity) and two different insulation materials, extruded polystyrene (XPS) and expanded polystyrene (EPS). As a result of this study, it was determined that XPS insulation materials offered an optimum thickness ranging from 1.20 to 8.10 cm, provided an energy savings between 15.38% and 69.90%, and required payback periods between 3.02 and 0.90 years, while EPS insulation materials offered an optimum thickness ranging between 2.00 and 11.80 cm, provided an energy savings between 21.82% and 70.61%, and required payback periods between 2.64 and 0.78 years, depending on the cities and fuel types. The lowest values of reduction of CO2 emission (39.82%) were obtained for Antalya when XPS and natural gas are used as optimum insulation material while Erzurum has the highest value (83.98%) for EPS and LPG. Highlights: Determining the optimum insulation thicknesses for poultry buildings. Evaluating energy savings for different fuels and different insulation materials. Estimating the reduction of CO2 emissions for four cities in different climate zones. Determining the payback periods for different regions, insulation materials and fuels.